2002
DOI: 10.1046/j.1471-4159.2002.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

D1 dopamine receptor stimulation increases GluR1 surface expression in nucleus accumbens neurons

Abstract: The goal of this study was to understand how dopamine receptors, which are activated during psychostimulant administration, might influence glutamate-dependent forms of synaptic plasticity that are increasingly recognized as important to drug addiction. Regulation of the surface expression of the a-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptor subunit GluR1 plays a critical role in longterm potentiation, a well-characterized form of synaptic plasticity. Primary cultures of rat nucleus accumben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 55 publications
(56 reference statements)
6
106
0
Order By: Relevance
“…For example, in the study of Thomas et al (2001), synaptic depression following repeated cocaine was observed in the shell but not the core of the NAcc while the core but not the shell subregion has been reported to contribute to reinstatement of cocaine seeking (McFarland and Kalivas, 2001). In addition, while some NAcc medium spiny neurons undergo whole cell and synaptic depression following drug exposure (Zhang et al, 1998;Thomas et al, 2001), NAcc interneurons display a more robust increase in GluR1 surface expression in response to D1 DA receptor activation (Chao et al, 2002) and may represent important targets for AMPA in the context of the present findings. Enhanced stimulation of these interneurons could possibly lead to enhanced inhibition of select medium spiny neurons (Pennartz and Kitai, 1991).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…For example, in the study of Thomas et al (2001), synaptic depression following repeated cocaine was observed in the shell but not the core of the NAcc while the core but not the shell subregion has been reported to contribute to reinstatement of cocaine seeking (McFarland and Kalivas, 2001). In addition, while some NAcc medium spiny neurons undergo whole cell and synaptic depression following drug exposure (Zhang et al, 1998;Thomas et al, 2001), NAcc interneurons display a more robust increase in GluR1 surface expression in response to D1 DA receptor activation (Chao et al, 2002) and may represent important targets for AMPA in the context of the present findings. Enhanced stimulation of these interneurons could possibly lead to enhanced inhibition of select medium spiny neurons (Pennartz and Kitai, 1991).…”
Section: Discussionmentioning
confidence: 50%
“…To the extent that these events have been suggested to accompany synaptic plasticity in different preparations (eg Benke et al, 1998;Lee et al, 2000Lee et al, , 2003, it is conceivable that they may underlie enhanced behavioral responsiveness to NAcc AMPA in a manner that is unrelated to overall AMPA receptor subunit expression. Interestingly, D 1 DA receptor activation increases the insertion of the GluR1 AMPA receptor subunit into the cell surface, and possibly synaptic sites, of NAcc cultured neurons through a pathway dependent on protein kinase A (Chao et al, 2002;Mangiavacchi and Wolf, 2004). Together with recent findings showing that enhanced, but not acute, NAcc AMPA induced reinstatement of drug seeking is DAdependent and accompanied by enhanced DA overflow in this site (Suto et al, 2003b;cf, Pierce et al, 1996a), these findings suggest a mechanism (enhanced D 1 DA receptor activation) whereby previous drug exposure could enhance NAcc AMPA receptor mediated transmission and generation of behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of our current study, the resulting increase in dopaminergic signaling is very likely a significant contributor to the induction of drug-induced depotentiation in the NAc shell. For example, while DA D1 receptor activation has been shown to promote the delivery of AMPARs to the surface of NAc MSNs (Chao et al, 2002), after repeated bouts of DA exposure, this effect of D1R activation is lost (Sun et al, 2008). Furthermore, a recent study found that prolonged ex vivo D1 receptor activation, while having no effect on AMPARs in NAc shell MSNs during the first several days of abstinence from cocaine self-administration, reduced the AMPAR/NMDAR if delivered following several weeks of abstinence (Ortinski et al, 2012).…”
Section: Mechanisms Underlying Synaptic Depotentiationmentioning
confidence: 99%
“…An increased surface-to-intracellular ratio of glutamate-1 receptors (GluR1) has been observed 21 days after the last injection of cocaine, suggesting a slowly developing redistribution of AMPA receptors to the surface of nucleus accumbens neurons, particularly in those lacking GluR2 (Boudreau and Wolf, 2005;Conrad et al, 2008). The increases in cell-surface AMPA receptors depends on activation of dopamine D 1 receptors and subsequent protein kinase A signaling (Chao et al, 2002). Functionally, overexpression of GluR1 in the nucleus accumbens facilitated extinction of cocaine-seeking responses (Sutton et al, 2003) and increased brain stimulation reward thresholds, reflecting decreased reward and possibly decreased motivated behavior (Todtenkopf et al, 2006).…”
Section: Ventral Striatum: Incentive Salience Pathways Salience Attrmentioning
confidence: 99%